The internal tension to the concept of autonomy -autonomy, reasons and republicanism- - Caviglia Marconi, Alessandro (2019)
The present work search to clarify some central point with regard to the republican tradition such as the place that the justice occupies, the exchange of reasons and the autonomy in it. That is why starts developing a clarification of what is meant by autonomy, the place it occupies in the moral tradition of the West, as well as presenting the dialectic internal to the same concept of autonomy, dialectic nourished by the requirement of exchange of reasons. Once this is done, presents how the concept of autonomy is inserted in the republican tradition submitted by Philip Pettit, and how this should be corrected taking into account the conception of justice developed by Rainer Forst.